Detection of the White Dwarf Spin of the Long-orbital Period Magnetic Cataclysmic Variable V1082 Sgr - Lima, I. J. (2025)
We report on the discovery of circular polarization modulated with a period of 1.943 ± 0.002 hr in the cataclysmic variable V1082 Sgr. These findings unambiguously reveal the rotation of a magnetic white dwarf and establish its intermediate polar nature. Along with its extraordinary long orbital period (Porb) of 20.8 hr, the spin period (Pspin) places this system in an extreme position of the Pspin versus Porb distribution. The circular polarization phase diagram has a single peak and an amplitude smaller than 1%. These data were used to model the postshock region of the accretion flow on the white dwarf surface using the CYCLOPS code. We obtained a magnetic field in the white dwarf pole of 11 MG and a magnetospheric radius consistent with the coupling region at around 2–3 white dwarf radii. The Pspin/Porb value and the estimated magnetic field momentum suggest that V1082 Sgr could be out of spin equilibrium or in a spin-up state, possibly in a stream accretion mode.